Pengelolaan Administrasi Data Bantuan Hukum YLBH BABEL Berbasis Web Dengan Model FAST - Wishnu Aribowo Probonegoro; Sujono Sujono; Lili Indah Sari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Website-based technology, networks, the internet, are technological advances that are often used today, where the development is quite rapid and is used by many people, and in various fields, one of which is the field of law. Legal Aid is a legal service provided by legal aid providers free of charge to legal aid recipients. The Legal Aid Foundation (YLBH) Bangka Belitung is one of the Legal Aid Institutions in Indonesia located in Pangkalpinang. This Legal Aid Institute was established with the aim of providing free legal aid services to people who need legal assistance, but are unable, legally blind and oppressed. The process of providing legal aid has many problems and shortcomings. Existing problems. The administrative data management process for the provision of legal aid is not well organized, the data recording of legal aid applicants is still done conventionally, there is no evidence of submission of the required files and files sometimes forget to record, this causes the data of legal aid applicants to be invalid, and the length of the reporting process each month. In this study, the author uses the FAST (Framework for the Application of System Thinking) model. It is hoped that with this web-based information system, it will facilitate the administrative processing of the application for legal aid, filing documents more neatly, efficiently, effectively and simplifying the process of searching for data, information needed, and reporting can also be faster